Cystic Adventitial Disease of the Common Femoral Artery: A Rare-Case Report - Wang, Qilong; Cheng, Zhihua; Tang, Liang; Wang, Qi; Zhang, Ping; Zhang, Hua (Frontiers in Surgery, 2022)
In this work, we report the case of a 59-year-old man with intermittent claudication of approximately 100 meters, who complained of resting pain in his lower right extremity. A pelvic, contrast-enhanced, computed tomography scan showed that there was cystic density in the lower segment of the right common femoral artery. Faced with the patient's risk of acute limb ischemia, we went through a difficult diagnostic procedure to choose an appropriate treatment for him. Additionally, we performed a pathological investigation of the excised common femoral artery following the excision bypass. On the fifth postoperative day, the patient was discharged from the hospital. During the 2-year follow-up, no new cysts were discovered in this patient. His prognosis was favorable.